超音波法による農業用ＰＣ管水路の非破壊診断の研究 - 石黒, 覚; ISHIGURO, Satoru (三重大学, 2011)
application/pdf コンクリート構造物の非破壊検査技術である横波超音波共振法を適用し,試験体を用いた探傷実験を行った.その結果,試験体の模擬損傷検出が可能であることを確認でき,本検査手法の有効性を示す結果を得た.既存の水路構造物には,強度・耐久性に優れ,施工性も良いことからPC管等のコンクリート二次製品が多く用いられている.本検査手法を土中に埋設施工されたPC管に適用し,炭酸性侵食等による管外面の損傷検査に対して有効な結果を得た. It experimented with the examination object by using the shear wave resonating method that was the non-destructive testing technology of a concrete structure. As a result, it was able to be confirmed to be able to detect mock damage of the examination object, and obtained the result of showing the effectiveness of this technique. A lot of concrete products such as PC tubes are used from excelling in strength and durability, and construct good for an existing waterway structure. The test method was applied to confirm the outside damage of PC tubes laid underground in the soil where damage occurs are seen by the Carbonic acid corrosion. The results showed the effectiveness of the test method. 平成20~22年度科学研究費補助金(基盤研究(C))研究成果報告書 20580262 research report